Influencer Marketing and Behavioral Guidance Towards Responsible Consumption: The Case of Cosmetic Products in Cameroon - Boubakary, Ben; Aboubakar, Aichatou (Archives of Business Research, 2025)
This study investigates the role of influencer marketing in fostering responsible consumption of cosmetic products in Cameroon. Drawing on a qualitative survey conducted with 60 participants, two major findings emerge. First, influencers act as channels of awareness-raising, yet their contribution remains ambivalent—oscillating between perceived authenticity and the pursuit of commercial opportunities. Second, while their recommendations shape purchasing decisions, this influence is contingent upon the level of trust consumers place in them and the degree of skepticism they express. The analysis further identifies the criteria that underpin influencers’ credibility and legitimacy, as well as the specific barriers to adopting responsible consumption practices linked to consumer habits and local market constraints. Overall, the study enhances understanding of the dynamics of influencer marketing in an understudied African context and offers insights for strengthening the effectiveness of campaigns through improved credibility management and the contextualization of messages.